ChemInform Abstract: Direct Catalytic Asymmetric Aldol Reaction of an α‐Azido Amide. Issue 37 (September 2015) - Weidner, Karin; Sun, Zhongdong; Kumagai, Naoya; Shibasaki, Masakatsu
Abstract The asymmetric aldol reaction of α‐aza‐indolinylamide (I) with aldehydes is studied in the presence of mesitylcopper as catalyst.